Dibalik Perilaku Kecanduan Chiki Berhadiah: Judi Atau Hiburan? (Studi Kasus Pada Fenomena Live Tiktok Shop) - Syafira, Tania Anindia; Khoirunnisa, Farida; Rauly Sijabat (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
The development of live streaming commerce through TikTok Shop has introduced new patterns of digital consumption that blur the boundaries between entertainment and speculative activities. One notable phenomenon is the purchase of prize-based snack products (chiki berhadiah), where consumers buy snacks with the expectation of receiving cash rewards. This study aims to examine the social meanings, perceptions, and consumers’ emotional and consumptive experiences related to this phenomenon in TikTok Shop live streams. Using a qualitative case study approach, data were collected through in-depth interviews, observation, and documentation. The findings indicate that prize-based snacks are perceived as a form of digital entertainment; however, they contain speculative elements similar to gambling, reflected in reward uncertainty, repeated purchasing behavior, and emotional drives such as curiosity and dissatisfaction. The study concludes that prize-based snack consumption represents a hybrid practice between entertainment and light gambling within the digital space.